2013
DOI: 10.1186/1477-3155-11-32
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent effects of microglial inhibition in vivo on Alzheimer’s disease neuropathology using bioactive-conjugated iron oxide nanoparticles

Abstract: BackgroundTau dysfunction is believed to be the primary cause of neurodegenerative disorders referred to as tauopathies, including Alzheimer’s disease, Pick’s disease, frontotemporal dementia and Parkinsonism. The role of microglial cells in the pathogenesis of tauopathies is still unclear. The activation of microglial cells has been correlated with neuroprotective effects through the release of neurotrophic factors and through clearance of cell debris and phagocytosis of cells with intracellular inclusions. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…Another approach is to fight tau dysfunctions, which are suspected to be behind many disorders like Alzheimer′s disease, Pick's disease or Parkinsonism. In a recent work, Glat et al72 demonstrated the beneficial effect of a fibrin peptide conjugated to γ‐Fe 2 O 3 (maghemite) in reducing the activation of microglial cells in rTg4510 mutant mice, which resulted in a reduced number of neurons with the undesired tangles compared to animals not treated with the therapeutic nanoparticles.…”
Section: Mh‐based Applications With Core–shell Npsmentioning
confidence: 99%
“…Another approach is to fight tau dysfunctions, which are suspected to be behind many disorders like Alzheimer′s disease, Pick's disease or Parkinsonism. In a recent work, Glat et al72 demonstrated the beneficial effect of a fibrin peptide conjugated to γ‐Fe 2 O 3 (maghemite) in reducing the activation of microglial cells in rTg4510 mutant mice, which resulted in a reduced number of neurons with the undesired tangles compared to animals not treated with the therapeutic nanoparticles.…”
Section: Mh‐based Applications With Core–shell Npsmentioning
confidence: 99%
“…Adams et al (2007) conjugated fibrin γ377-395 peptide [one fibrin-derived peptide that can inhibit microglial activity in vivo specifically to iron oxide (γ-Fe 2 O 3 ) nanoparticles with diameters 21 ± 3.5 nm] in order to counteract the short half-life of the peptide. The study showed that, compared to the free peptide of the same concentration, γ-Fe 2 O 3 nanoparticles could specifically inhibit the microglial cells in rTg4510 tau-mutant mice, supporting the fact that the nanoparticles can be used for the delivery of substances to the brain and for providing a possible therapeutic strategy to neurodegenerative tauopathies (Glat et al, 2013). Kouyoumdjian et al (2013) reported a biomimetic path using glyconanoparticles-SPIO to detect Aβ.…”
Section: Application Of Iron Oxide Nanoparticles In the Treatment Of Admentioning
confidence: 80%
“…They have features such as paramagnetic superpower, high saturation field, nontoxicity, biodegradability, and variable loops. 9,10 Studies conducted on the effect of magnetically charged nanoparticles showed that the application of these nanoparticles as a carrier can be appropriate in treatment of many diseases. In addition, these nanoparticles, in fibrillation process, can have a crucial role in decreasing or delaying the plaque formation mechanism in A-proteins.…”
mentioning
confidence: 99%